Impactos do mercado livre de energia elétrica no Brasil nas tarifas regionais do mercado cativo: uma análise de relações entre variáveis. - Cardoso, Flávio Gomes (2024)
Context: Contextualization: Reforms in Brazil's electricity sector transformed the traditional state monopoly model with the introduction of the free energy market. This created two trading environments for the same asset (KWh of energy), with distinct prices in the free market and the regulated (captive) market. This new reality presented challenges for regional utilities, which lost large consumers to the free market and had to adjust rates in the captive market to prevent a system collapse. Objective: The aim of this study is to investigate the impacts of policy changes in Brazil's electricity market, specifically the introduction of the free market, on the rates for regional captive/regulated consumers. Method: Public data from ANEEL and CCEE from 2013 to 2024 were collected to relate, through linear regressions, the free market price, captive market tariffs, and consumer migration between markets. Results: The research reveals that free market prices and consumer migration directly impact captive market tariffs, as evidenced by three regressions showing these effects. It indicates that captive and free markets are also interconnected for CEMIG in the Triângulo Mineiro region, demonstrated by three regressions highlighting the impacts on CEMIG’s regional tariffs. The captive market shows a constant increase in tariffs, inversely related to the declining prices in the free market and directly related to the number of migrated consumers. Thus, the decrease in free market prices and migration elevate tariffs in the captive market, demonstrating an unexpected interdependence between these variables. Relevance to the Concentration Area (Regionality and Management): The research aligns with the PPGAdm concentration area and the "Regionality and Management" research line, as it focuses on the energy utility of the Triângulo Mineiro, CEMIG, analyzing the regional influence of consumer migration and the tariff impacts stemming from this dynamic. Impact and Innovative Aspect: This work fills a gap by investigating the inverse effect of the free market on captive market tariffs, especially for consumers unable to migrate. It contributes to understanding the effects of the free market on tariffs. Economic, Social, and Regional Impact: The study holds managerial and regional relevance, focusing on CEMIG. It demonstrates how migration to the free market impacted the company’s revenue and the rates applied to captive consumers. The research connects data from ANEEL and CCEE, showing the dynamics between the two markets. 11 Regional Implications: The research reveals regional impacts on CEMIG, where the loss of large consumers to the free market resulted in rate adjustments. Sustainable Development Goals (SDGs): The study contributes to the UN’s 2030 Agenda SDG 7, promoting universal and affordable energy access by considering the effects of rate changes and the free market on electricity access.